Question
upstudy study bank question image url

Sowe for \( x \) and \( y \) simutanously \( 2 x-y=8 \) \( y=x^{2}+4 x-23 \) 12

Ask by Maxwell Gough. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are \( x = -5, y = -18 \) and \( x = 3, y = -2 \).

Solution

Solve the system of equations \( 2x-y=8;y=x^{2}+4x-23 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x-y=8\\y=x^{2}+4x-23\end{array}\right.\) - step1: Substitute the value of \(y:\) \(2x-\left(x^{2}+4x-23\right)=8\) - step2: Simplify: \(-2x-x^{2}+23=8\) - step3: Move the expression to the left side: \(-2x-x^{2}+23-8=0\) - step4: Subtract the numbers: \(-2x-x^{2}+15=0\) - step5: Factor the expression: \(\left(-x+3\right)\left(x+5\right)=0\) - step6: Separate into possible cases: \(\begin{align}&-x+3=0\\&x+5=0\end{align}\) - step7: Solve the equation: \(\begin{align}&x=3\\&x=-5\end{align}\) - step8: Calculate: \(x=3\cup x=-5\) - step9: Rearrange the terms: \(\left\{ \begin{array}{l}x=3\\y=x^{2}+4x-23\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=x^{2}+4x-23\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(-5,-18\right)\cup \left(x,y\right) = \left(3,-2\right)\) The solutions to the system of equations \(2x-y=8\) and \(y=x^{2}+4x-23\) are \((-5,-18)\) and \((3,-2)\).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To solve for \( x \) and \( y \) simultaneously using the two equations: 1. From the first equation, \( 2x - y = 8 \), we can express \( y \) in terms of \( x \): \[ y = 2x - 8 \] 2. Substitute \( y = 2x - 8 \) into the second equation \( y = x^2 + 4x - 23 \): \[ 2x - 8 = x^2 + 4x - 23 \] 3. Rearranging gives: \[ 0 = x^2 + 4x - 23 - 2x + 8 \] \[ 0 = x^2 + 2x - 15 \] 4. Now factor the quadratic: \[ (x - 3)(x + 5) = 0 \] Therefore, \( x = 3 \) or \( x = -5 \). 5. Now, substitute these \( x \) values back into \( y = 2x - 8 \): For \( x = 3 \): \[ y = 2(3) - 8 = 6 - 8 = -2 \] For \( x = -5 \): \[ y = 2(-5) - 8 = -10 - 8 = -18 \] Thus, the solutions are: 1. \( (x, y) = (3, -2) \) 2. \( (x, y) = (-5, -18) \) Now you have two points where the equations intersect! Isn't it cool how algebra can connect those dots? Keep diving into the world of equations; it's like a treasure hunt for solutions!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy